Practical research 2 - Baraceros, Esther L. (Sampaloc, Manila : Rex Book Store, Inc., 2016)
"This book comprehensively deals with the aspects of quantitative research, an inquiry method that centers on the production of evidence-based findings. Aiming at communicating to people through varies ways and strategies to discover the veracity or genuineness of something, this book puts premium on the accuracy and objectiveness of any knowledge acquisition and production in relation to these components of quantitative research: research problem, research questions, hypotheses formulation, research design, research methodologies, variables, sampling procedure, and research-writing styles, among others."
Includes references and index.
English text.
Keywords: Research; Quantitative research